Climate finance for agricultural adaptation - Ye W; Vasileiou, Ioannis; Förch, Wiebke (2016)
Climate finance has largely focused on non-agricultural sectors, while finance for adaptation remains to be largely unexplored. This paper takes stock of existing funds for agricultural adaptation and compares different elements across these.